Nuclear power hazard control policy - Chicken, John C. (Pergamon Press, 1982)
Nuclear Power Hazard Control Policy presents an analysis of the factors that appear to have influenced the formation and form of nuclear power hazard control policy in Britain. Particular attention is directed to those political groups that have developed a special interest in the problems of nuclear power, and to the interplay between organized groupings and public opinion generally. The metamorphosis of these groupings is traced from the origins of the nuclear industry in World War II to their prominent role during the Windscale Inquiry. This volume is comprised of nine chapters and begins with a simple account of the technical nature of nuclear hazards and of the legal and administrative framework that has been developed to control them. The subsequent chapters concentrate primarily on the influence exerted by social and political factors. Throughout the study, emphasis is given to the policy constraint imposed by increased expectations in the form of demands for higher standards of living, as well as improvements in the quality of the environment. The final chapter describes a model of the policy-making system that takes account of the consequences of variation with time in the environment surrounding the system. Appendices are included to provide a chronology of the relevant events and a summary of the administrative arrangements that various countries have made to control the safety of nuclear reactors. This monograph will be of value to policymakers concerned with the hazards of nuclear power and how to control them.--Provided by publisher.